Hyperglycemia-induced oxidative stress and epigenetic regulation of ET-1 gene in endothelial cells - Binjawhar, Dalal Nasser; Alhazmi, Alaa T.; Bin Jawhar, Wejdan Nasser; MohammedSaeed, Walaa; Safi, Sher Zaman (Frontiers in Genetics, 2023)
Hyperglycemia-induced endothelial dysfunction and the subsequent increase in reactive oxygen species (ROS) play an important role in the regulation of genes in diseases such as diabetes and other cardiovascular complications. The purpose of this study was to evaluate the hyperglycemia-induced oxidative stress, and investigate the possible effect of hyperglycemia on the expression and methylation of ET-1 gene in in human umbilical vein endothelial cells (HUVEC). Cells were cultured in endothelial cell growth medium with normal (5 mM) and high (25 mM) glucose concentrations to mimic a diabetic condition. Computational analysis were performed using UCSC genome browser and eukaryotic promoter database (EPD). Real time PCR was used to check the gene expression profile of ET-1 gene. Glucose-induced cytotoxicity and oxidative stress were determined by MTT and DCFH-DA assays respectively. Promoter methylation was assessed by the bisulfite sequencing method. DCFH-DA assay showed that hyperglycemia can significantly increase the level of reactive oxygen species (ROS) in HUVECs. Glucose exposure also significantly increased the expression of ET-1 gene. MTT assay showed a marked decrease in the viability of cells due to the glucose induced damage. Methylation analysis revealed hypomethylation of the promoter of ET-1 however the difference was not significant. Out of 175 CpGs at 25 CpG sites, only 36 CpGs were methylated (20.5% methylation) in cell treated with normal glucose. Upon exposure to high glucose only 30 CpGs were methylated in 175 CpGs at 25 CpG sites (17.1% methylation). Our study concludes a significantly high expression of ET-1 gene in response to high glucose exposure in HUVECs. It also reports that hyperglycemic condition leads to elevated oxidative stress and reduce cell viability. No significant change was found in methylation when cells were treated with high and low glucose concentrations.